2011
DOI: 10.1007/s10439-011-0391-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Position Sensitivity Study in the Electrocardiographic Forward Problem Using Stochastic Collocation and Boundary Element Methods

Abstract: The electrocardiogram (ECG) is ubiquitously employed as a diagnostic and monitoring tool for patients experiencing cardiac distress and/or disease. It is widely known that changes in heart position resulting from, for example, posture of the patient (sitting, standing, lying) and respiration significantly affect the body-surface potentials; however, few studies have quantitatively and systematically evaluated the effects of heart displacement on the ECG. The goal of this study was to evaluate the impact of pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 30 publications
0
44
0
4
Order By: Relevance
“…Regarding uncertain locations and orientations of sources in the electrocardiographic (ECG) forward problem, Swenson et al [35] used the gPC method in combination with a sampling based on sparse Smolyak grids to predict changes in heart location and orientation on body-surface ECG potentials. The advantage of such a non-intrusive formulation of the gPC method is that the underlying deterministic model describing the bio-electrical application can remain unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding uncertain locations and orientations of sources in the electrocardiographic (ECG) forward problem, Swenson et al [35] used the gPC method in combination with a sampling based on sparse Smolyak grids to predict changes in heart location and orientation on body-surface ECG potentials. The advantage of such a non-intrusive formulation of the gPC method is that the underlying deterministic model describing the bio-electrical application can remain unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of geometry, the larger variations are found for the heart long axis angle. Swenson et al [17] also revealed the importance of cardiac angulation in the ECG forward problem. Another study showed that ECG imaging is sensitive to global anatomical parameters such as the heart orientation and location with regard to the lead positions [18].…”
Section: B Reference Anatomy In Ecgimentioning
confidence: 99%
“…Swenson et al [3] created a geometric model consisting of triangular elements representing the heart and torso tank surfaces and supposed significant potential variations, especially ST-segment voltage changes by postural change. These variations seemed to be more pronounced for a heart exhibiting increased ischemic potential.…”
Section: Introductionmentioning
confidence: 99%